2017
DOI: 10.1007/s13595-016-0601-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of models for estimating bark thickness of Picea abies in southwest Germany: the role of tree, stand, and environmental factors

Abstract: & Key message Bark thickness was shown to vary between regions, stands, and trees. Bark thickness prediction equations of different model complexity can be suggested depending on the purpose of application. Site and stand conditions, which influence variation of growth rate to a large extent, seem to have a strong influence on bark thickness, with better site quality leading to smaller relative bark thickness. & Context For many applications in forestry and forest science, local or regional species-specific ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
7
27
0
1
Order By: Relevance
“…The bark thickness showed an increasing linear pattern and strong correlation with the diameter (di) of the Teak trees' log ( Figure 1), similar to that observed by Cordero and Kanninen (2003) for the same species in different regions of Costa Rica, Kitikidou et al (2014) for Pinus halepensis in northern Greece and Stängle et al (2017) for Piceaabies in southwestern Germany. Thus, the variable di is widely employed as an independent model for the relationship between the diameter with and without bark at any height of the stem.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The bark thickness showed an increasing linear pattern and strong correlation with the diameter (di) of the Teak trees' log ( Figure 1), similar to that observed by Cordero and Kanninen (2003) for the same species in different regions of Costa Rica, Kitikidou et al (2014) for Pinus halepensis in northern Greece and Stängle et al (2017) for Piceaabies in southwestern Germany. Thus, the variable di is widely employed as an independent model for the relationship between the diameter with and without bark at any height of the stem.…”
Section: Discussionsupporting
confidence: 81%
“…For many conifer species, for example, it has been found that tree thickness can be described by variables inherent to the tree, such as bark diameter, total height, age, and measurement position (LAASASENAHO et al, 2005;LI;WEISKITTEL, 2011;TEWARI;MARISWAMY, 2013;STÄNGLE et al, 2017). In some cases, there is influence of site index on bark thickness, as reported by Božić et al (2007) for Abies alba.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Bark thickness, wood density and heartwood proportion vary with genotype, site conditions, tree age, growth rate and position within the stem (Pillai et al 2013, Stängle et al 2017, Wu et al 2011. Plantation-grown wood of tropical acacia species typically has low to moderate basic density (Chowdhury et al 2005, Hai et al 2008.…”
Section: Comparing Wood Density Heartwood Proportion and Bark Thicknmentioning
confidence: 99%